Use of contraception by women treated with leflunomide due to rheumatic arthritis. (January 2014) - Banas, T.; Hadyla-Banas, I.; Pityński, K.; Bereza, K.; Migdal, M.; Batko, B.
<x xml:space="preserve">Abstract</x> A total of 46 premenopausal patients treated with leflunomide (LMF) for rheumatic arthritis (RA) and 107 women of reproductive age free from chronic diseases were investigated to evaluate methods of contraception. Among 31 LMF-treated women using contraception, 48.4% chose oestrogen-progesterone hormonal contraception (E-PHC); 16.1% condoms; 3.2% had an intrauterine device and 32.0% preferred natural methods. These methods differed significantly from women in the control group, who mostly used condoms (56.8%) and E-PHC (35.3%) and rarely, natural methods (3.95%) or progesterone injections (3.95%). As many as 32.6% LMF-treated patients did not use any method of birth control. The choice of contraception among RA patients with LFM therapy was significantly dependent on the experience with methods used prior to the LFM therapy introduction (p < 0.001). Compared with women free from chronic diseases, LMF-treated patients use E-PHC significantly more often but still as many as 33% do not use any contraceptive method, despite strong recommendations.